Comparing mission statements of social enterprises and corporate enterprises in the new and renewable energy sector of India: A computer aided content analysis study - Subhanjan Sengupta; Arunaditya Sahay (Journal of Global Entrepreneurship Research, 2017)
This paper aims to explore how differently corporate enterprises and social enterprises strategically position themselves through their mission statements. The most notable distinctions between the mission statements of both groups exist in the degree of action orientation, endorsements of people/groups, and the highlights of positive entailment. The new and renewable energy sector is playing a key role in the emergence of India as an environmentally conscious emerging economy. The enterprises instrumental in this change are both social and corporate enterprises. While technology is important, a key factor to success is strategic approach. The vision and mission statements are strategically crafted by organizations to position themselves in the industry. This motivated the authors to carry out a comparative analysis of the mission statements of social and corporate enterprises to learn about the existing differences. Efforts were employed to quantify the narrative style and tonality of mission statements by applying DICTION software. This process generated values for the 'master variables' and 'calculated variables' in mission statements. Content analysis revealed that while a significant number of enterprises scored zero for the calculated variable 'insistence', only a few had scores within range. Most enterprises scored considerably well in the master variable 'activity'. In 'optimism' social and corporate enterprises show some noticeable differences in their purpose, which reflect how different these organizations are. This content analysis succeeds in reflecting where the social and corporate enterprises in India's renewable energy sector differ in their strategic intent. While in renewable energy social enterprises there is a domination of reference to beneficiaries/communities in their mission statements, and the positive entailments in terms of social change; renewable energy corporate enterprises seem to have a stronger intent to focus on issues related to technology, innovation, efficiency, and cost-leadership. Thus, this paper not only adds to establishing the fact that mission statements do play an important role in reflecting the strategic purpose of the organization, but adds to the arguments on the difference between social and commercial entrepreneurship.
Keywords: 650; Enterprise; New and renewable energy; Mission statements; Content analysis